An econometric analysis of evaluation and improvement of budget performance in local government: Array - Lulaj, Enkeleda; Muthmainnah (Acta Universitatis Danubius. Œconomica, 2021)
This paper provides a summary of studies focusing on the use of budget information in performance evaluation and improvement during budget governance. The survey shows that studies have accepted that this information is used in different ways. In this case, various factors have been identified for evaluating and improving budget performance in local governments. Despite this breadth of analysis, a critical review of the literature shows that in recent years local governments need to improve budget indicators to increase performance. Furthermore, this empirical study tends to guide local governments in choosing the right methodology for improving and evaluating budget performance. The research was conducted in local governments through a questionnaire that gave very important recommendations for budget performance.